2017
DOI: 10.1007/s40097-017-0226-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel nitrogen dioxide gas sensor based on TiO2-supported Au nanoparticles: a van der Waals corrected DFT study

Abstract: The interactions of nitrogen dioxide molecule with TiO 2 -supported Au nanoparticles were investigated using density functional theory. Surface Au atoms on the TiO 2 -supported Au overlayer were found to be the most favorable binding sites, thus making the adsorption process very strong. Both oxygen and nitrogen atoms of the NO 2 molecule can bind to the Au surface by forming strong chemical bonds. The adsorption of NO 2 molecule on the considered structures gives rise to significant changes in the bond length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…All theoretical calculations in this paper are based on the density functional theory (DFT) in Materials Studio (MS) [32,33]. The model construction, optimization and parameter calculation were completed by the DMol 3 module [34].…”
Section: Computational Detailsmentioning
confidence: 99%
“…All theoretical calculations in this paper are based on the density functional theory (DFT) in Materials Studio (MS) [32,33]. The model construction, optimization and parameter calculation were completed by the DMol 3 module [34].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Moreover, the effect of the addition of Au nanoparticles (5 nm) is investigated, which are selected to improve the water adsorption and to obtain improved transient response in terms of response and recovery times. The addition of Au nanoparticle allows the formation of Au/TiO 2 interfaces, which were proven to enhance water adsorption activity [16][17][18] and to act as favorable binding sites for different gases, providing faster response and recovery times [19][20][21][22]. It should be noted that the activation barrier for the dissociation of H 2 O at the Au-TiO 2 interface is substantially smaller than on the supported gold nanoparticle (0.6 eV vs. 1.3 eV) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating Au into the TiO 2 surface is an example of chemical sensitization, as Au favors the connection between the molecules of the target gases and the metallic network. Abbasi and Sardroodi [105] made Au/TiO 2 sensors for the detection of NO 2 , where they revealed that the atoms that make up the target gas chemically bond to Au. This agrees well with Chomkitichai et al [106], who concluded that the H 2 gas detection performance increased with the introduction of 0 to 0.75% Au in TiO 2 .…”
Section: Tio 2 -Doping or Assistant Metalsmentioning
confidence: 99%